2014
DOI: 10.1007/s10571-014-0138-6
|View full text |Cite
|
Sign up to set email alerts
|

Activation of 5-HT2C Receptor Promotes the Expression of Neprilysin in U251 Human Glioma Cells

Abstract: Abeta accumulation, a hallmark of Alzheimer's disease, promotes the disease progress in multiple facets. Abeta is formed through amyloidogenic cleavage pathway of amyloid precursor protein (APP). Production of Abeta can be decreased via activation of 5-HT2C receptor, which enhances alternative APP non-amyloidogenic cleavage. Besides, as one of the best characterized Aβ degrading enzymes, neprilysin (NEP) in AD progress has drawn more and more attention. We investigated whether there exists any connection betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In good agreement, pharmacological activation of 5-HT 4 receptors was shown to enhance short- and long-term memory function (Meneses, 2007), endorsing the hypothesis of a putative role of these drugs for the amelioration of symptomatology of depression in AD. With regard to other receptor subtypes, it has been shown that APP can be released upon activation of 5-HT 2A and 5-HT 2C , and activation of 5-HT 2C receptor promotes the expression of neprilysin, a well-characterized Aβ degrading enzymes (Tian et al., 2015). However, it should be considered that both 5-HT 2C agonists and antagonists have been evaluated as antidepressants (Cryan and Lucki, 2000; Steardo et al., 2000; Cryan et al., 2005).…”
Section: Monoamine System In Depression and Alzheimer’s Diseasementioning
confidence: 99%
“…In good agreement, pharmacological activation of 5-HT 4 receptors was shown to enhance short- and long-term memory function (Meneses, 2007), endorsing the hypothesis of a putative role of these drugs for the amelioration of symptomatology of depression in AD. With regard to other receptor subtypes, it has been shown that APP can be released upon activation of 5-HT 2A and 5-HT 2C , and activation of 5-HT 2C receptor promotes the expression of neprilysin, a well-characterized Aβ degrading enzymes (Tian et al., 2015). However, it should be considered that both 5-HT 2C agonists and antagonists have been evaluated as antidepressants (Cryan and Lucki, 2000; Steardo et al., 2000; Cryan et al., 2005).…”
Section: Monoamine System In Depression and Alzheimer’s Diseasementioning
confidence: 99%
“…As a transcript that is specifically expressed in the brain, HBII-52-14 may target the serotonin receptor (5HT-2C) in the brain, and regulate its functional methylation status [30,31]. Recent publications confirmed that the expression pattern of 5HT-2C, regulated by our identified snoRNA, is pathogenic and may be involved in the initiation and progression of low-grade glioma (LGG) [32]. This result implies that this parameter may be effective in differentiating glioma from other tumor subtypes.…”
Section: Discussionmentioning
confidence: 99%